Risk factors of cardiovascular diseases in rheumatoid arthritis - T V Popkova; D S Novikova; V V Pisarev; E S Mach; E L Nasonov (Научно-практическая ревматология)
Cardiovascular complications (CVC) including myocardial infarction (MI), sudden death and stroke (ST) are the main cause of premature mortality in rheumatoid arthritis (RA). Chronic inflammation plays the key role in the development of CVC in RA. Objective. To analyze prevalence of cardiovascular diseases (CVD), significance of traditional risk factors (Rf), DMARDs and RA features in the development of clinical and subclinical signs of atherosclerosis (AT). To compare results with data of QUEST-RA. Material and methods. Traditional Rf and CVD frequency in RA pts were assessed with a questionnaire. Coronary heart disease, MI and ST were diagnosed according to medical documents. Subclinical signs of atherosclerosis were evaluated with carotid artery sonography. Results. Traditional CVD Rf were evaluated in 563 pts (496 female, 93 male) aged 54 (44-54) years with disease duration 72 (24-144) months. Clinical signs of AT were revealed in5,6%, subclinical – in 11% of RA pts. Hyperlipidemia was present in 82%, increase of intima-media thickness – in 51%, family strain of CVD – in 44%, hypertension – in 38% of pts with RA. Traditional Rf, extra-articular features of RA, CVC and early AT signs weremore frequent in men than in women (p<0,005). Thickness of intima-media complex in 11men exceed that in women (p<0,005). RA pts were divided into two groups (I – with CVD and II – without CVD) to assess relationship between traditional Rf and CVC. Frequency of traditional Rf (hypertension and increased intima-media thickness) in group I was higher than in group II. Relative risk of their development was 4,78 and 2,09 respectively (p<0,05). 38% of RA pts had extra-articular features of RA (OR=2,02; p=0,04). Thickness of intima-media complex correlated with duration of treatment with hydroxichloroquine and sulfasalazine (r=0,34; p=0,0002 and r=0,28; p=0,008 respectively). CVC were not associated with administration of other DMARDs.